Clinical Oncology Society of Australia: Position statement on cancer‐related malnutrition and sarcopenia. Issue 4 (17th August 2020) - Kiss, Nicole; Loeliger, Jenelle; Findlay, Merran; Isenring, Elizabeth; Baguley, Brenton J.; Boltong, Anna; Butler, Alexis; Deftereos, Irene; Eisenhuth, Michelle; Fraser, Steve F.; Fichera, Rebecca; Griffin, Hayley; et al.
Abstract: This position statement describes the recommendations of the Clinical Oncology Society of Australia (COSA) regarding management of cancer‐related malnutrition and sarcopenia. A multidisciplinary working group completed a review of the literature, focused on evidence‐based guidelines, systematic reviews and meta‐analyses, to develop recommendations for the position statement. National consultation of the position statement content was undertaken through COSA members. All people with cancer should be screened for malnutrition and sarcopenia in all health settings at diagnosis and as the clinical situation changes throughout treatment and recovery. People identified as "at risk" of malnutrition or with a high‐risk cancer diagnosis or treatment plan should have a comprehensive nutrition assessment; people identified as "at risk" of sarcopenia should have a comprehensive evaluation of muscle status using a combination of assessments for muscle mass, muscle strength and function. All people with cancer‐related malnutrition and sarcopenia should have access to the core components of treatment, including medical nutrition therapy, targeted exercise prescription and physical and psychological symptom management. Treatment for cancer‐related malnutrition and sarcopenia should be individualised, in collaboration with the multidisciplinary team (MDT), and tailored to meet needs at each stage of cancer treatment. Health services should ensure a broad range of health care professionals across the MDT have the skills and confidence to recognise malnutrition and sarcopenia to facilitate timely referrals and treatment. The position statement is expected to provide guidance at a national level to improve the multidisciplinary management of cancer‐related malnutrition and sarcopenia.